Psychological Foundations of Personality Development in Cadet Pilots’ Sports and Health Activities - Mykola Piven; Oksana Zakharova; Olena Lopatiuk; Mykola Oleksyn; Ihor Mykhailichenko (North American Journal of Psychology, 2026)
The training of aviation professionals requires not only a high level of technical knowledge but also the development of psychological resilience, self-regulation, and the capacity for active personality development. The purpose of the study is to determine the impact of a programme integrating sports, health-promoting, and psychological interventions on the personality development and professional competencies of future pilots. The study involved 116 cadets aged 17–22 years, divided into an experimental group (58 participants) and a control group (58 participants). In the experimental group, a personality development algorithm was implemented, which included individual coaching, self-regulation training, and the pedagogical strategy “Challenge and Support” within the sports and health-promoting module. The data indicated positive trends in key psychological mechanisms in the group exposed to the formative intervention. In the experimental group, self-control increased by 28.3% (from 61.2±3.1 to 78.5±2.9 points, p